2022
DOI: 10.3390/jpm12101715
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dialysis Modalities on All-Cause Mortality and Cardiovascular Mortality in End-Stage Kidney Disease: A Taiwan Renal Registry Data System (TWRDS) 2005–2012 Study

Abstract: Introduction: End-stage kidney disease (ESKD) patients who need renal replacement therapy need to face a dialysis modality decision: the choice between hemodialysis (HD) and peritoneal dialysis (PD). Although the global differences in HD/PD penetration are affected by health-care policies, these two modalities may exert different effects on survival in patients with ESKD. Although Taiwan did not implicate PD as first policy, we still need to compare patients’ outcomes using two modalities in a nation-wise data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Patients receiving other forms of dialysis such as peritoneal dialysis were excluded. Combining data across different dialysis modalities could potentially impact mortality outcomes ( 56 ) and limit the generalizability of the findings to specific populations. By focusing our meta-analysis specifically on patients receiving hemodialysis, we were able to evaluate the GNRI-mortality association in a distinct patient group with shared characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving other forms of dialysis such as peritoneal dialysis were excluded. Combining data across different dialysis modalities could potentially impact mortality outcomes ( 56 ) and limit the generalizability of the findings to specific populations. By focusing our meta-analysis specifically on patients receiving hemodialysis, we were able to evaluate the GNRI-mortality association in a distinct patient group with shared characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Lasers are currently the dominant light sources for photobiomodulation. Until recently, lasers were thought to exert biologically beneficial effects; however, recent studies have suggested otherwise ( 34 , 35 ). The major difference between lasers and LEDs is the bandwidth.…”
Section: Discussionmentioning
confidence: 99%
“…According to the US Renal Data System (USRDS) 2021 report, Taiwan was one of the three countries with the highest rate of increase in the number of patients with end-stage kidney disease (ESKD) who required long-term dialysis 7 . And, it was estimated that about 91.4% of ESKD patients received hemodialysis (HD), and 8.6% received PD 8 . From 2009 to 2013, the 1, 3, and 5-year cumulative survival rates of ESKD patients undergoing maintenance hemodialysis were 89.4%, 69.6%, and 54.2%, respectively 9 .…”
Section: Introductionmentioning
confidence: 99%